(untitled) (Revista Archai, 2016)
This article intends to reconstruct the historiographical problem of Plato’s oral teachings: the so-called "unwritten doctrines". In parallel with the Dialogues, there is strong textual evidence of an oral transmission that many philologists try to track since the end of 18th century. The purpose of this article is, thus, to analyze not only the central passages and testimonia but also the main conjectures held by modern scholars on this subject, in order to sketch out the two resulting historiographical poles. On the one hand, some scholarship argues for the philological validity of Plato’s oral transmission and suggests that the theoretical positions attributed to him by those texts correspond to the authentic platonism (casting the Dialogues to a secondary plan). On the other hand, there are some modern authors that fully reject such claim, holding that there is no philological validity whatsoever in the textual tradition. This article is conceived as the first step of a wider project on Plato’s unwritten doctrines. Its main purpose is, thus, to provide a crosschecked reading of those two contrasting historiographical models, from which we may (in a second article) propose a wider position about the problem of Plato’s unwritten doctrines. Keywords: Plato, unwritten doctrines.